Literasi Keuangan: Menjelajahi Dunia Kartu Kredit Dan Kredit Dengan Bijaksana - Puput Iswandyah Raysharie; Yonatan Ari Santoso; Rinto Alexandro; Erni Dwi Puji Setyowati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The HR Assistance Lecturer (superior) activity at Palangka Raya University carries out financial literacy education with a focus on the theme "Exploring the World of Credit Cards and Credit Wisely." This activity aims to provide employees with an in-depth understanding of financial management, credit card management, and credit intelligence. Through this program, employees will be provided with comprehensive educational materials in the form of guides, brochures, and presentation materials. A digital-based interactive learning platform is also being developed to facilitate self-learning. In addition, a tracking and evaluation system was designed to measure the effectiveness of the activities. The program also includes promotional campaigns and financial literacy campaigns to raise public awareness of the importance of financial literacy. In order to strengthen the program, counseling and support services were provided for employees facing difficulties managing debt. A partnership plan with the bank was implemented to provide support, resources, and access to relevant banking services. This activity is expected to provide direct benefits to employees in improving their financial literacy competencies and providing the best service to the community in civil registration aspects that involve financial aspects